2015
DOI: 10.1055/s-0035-1564436
|View full text |Cite
|
Sign up to set email alerts
|

How Has the Robot Contributed to Colon Cancer Surgery?

Abstract: Robotic surgery is an emerging field in colorectal surgery and may overcome the limitations of conventional laparoscopic surgery, such as rigid instrumentation, poor ergonomics, and assistant-dependent camera movements and retraction. In addition, robotic-assisted colectomy appears to offer comparable outcomes to laparoscopic colectomy with limited long-term outcomes data. Prolonged operating time, increased costs and learning curve are the major drawbacks of robotic colectomy for colon cancer. Although new ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Beyond this, it has historically been challenging to truly calculate potential long-term cost savings for a given procedure. In colorectal surgery for example, the potential reduction in stoma rates for robotic low rectal resections could have a huge consequence for the health economics associated with the procedure, although this benefit is currently not proven [63]. Equally, reduced length of ICU admission or overall stay has cost effects [64].…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…Beyond this, it has historically been challenging to truly calculate potential long-term cost savings for a given procedure. In colorectal surgery for example, the potential reduction in stoma rates for robotic low rectal resections could have a huge consequence for the health economics associated with the procedure, although this benefit is currently not proven [63]. Equally, reduced length of ICU admission or overall stay has cost effects [64].…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…[2][3][4] Meanwhile, the robot-ic system provides magnified three-dimensional vision, better ergonomics, multiple articulated robotic instruments, and an opportunity to perform remote surgery. 5 In terms of the advantage to approach narrow pelvic cavity, robotic surgery has been used prominently in the urologic and gynecologic fields. In recent, robotic rectal surgery including a robot-assisted laparoscopic approach or totally robotic surgery is increasing and regarded as an effective and surgeon-convenient treatment option that is suggested to overcome the limitations of laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest case series of robotic TME (RTME) was published in 2006 by Pigazzi et al, 47 and since then several other studies have demonstrated the efficacy and safety of RTME and compared RTME. 29,35,37,[48][49][50][51][52][53][54][55][56][57][58][59][60][61] RTME was associated with lower conversion rates, and reduced rate of erectile dysfunction (ED) than laparoscopic TME in some studies. 49,60,62,63 Furthermore, of those who developed postoperative ED, patients in the robotic groups appeared to have a more rapid improvement of symptoms when assessed at 3 and 6 months.…”
Section: Total Mesorectal Excisionmentioning
confidence: 99%
“…(laparoscopic splenic flexure mobilization), single docking (mobilizing the second and third robotic arms for different parts of the surgery), double docking (docking once for splenic flexure mobilization, then redocking for the rest of the procedure), and recently a "single-position flip arm technique" that allows for splenic flexure mobilization and low anterior resection with only one docking position. [35][36][37] Although good outcome data are not as abundant as for robotic right colectomy, several studies have compared robotic versus laparoscopic left colectomy. [26][27][28][29][30]38 As seen with robotic right colectomy, robotic left colectomy had similar perioperative and oncologic outcomes with increased operative times.…”
mentioning
confidence: 99%